Low-temperature ion nitriding method for AerMet100 steel
By preheating, heat treatment and low-temperature ion nitriding treatment on AerMet100 steel, a nitriding layer is formed, which solves the problem of the degradation of the matrix hardness of the AerMet100 material in ion nitriding treatment, and improves its wear resistance and fatigue resistance.
Patent Information
- Application Number
- CN202411601815.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-11
AI Technical Summary
During the ion nitriding process, the AerMet100 material is prone to decrease the hardness of the matrix due to improper control of temperature and time, which affects its overall performance.
The low-temperature ion nitriding method is adopted to prepare the AerMet100 steel by preheating, heat treatment and low-temperature ion nitriding treatment to form a nitriding layer to improve wear resistance and fatigue resistance, while avoiding the reduction of matrix hardness.
Ion nitriding treatment is completed at a lower temperature, which avoids deformation of AerMet100 steel, and ensures that the matrix hardness does not decrease, improving the material's wear resistance and fatigue resistance.
Smart Images

Figure CN119392161A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heat treatment of metal materials, and in particular to a method for low-temperature ion nitriding of AerMet100 steel. Background Art
[0002] AerMet100 material is a high Co-Ni secondary hardened ultra-high strength steel. After proper heat treatment, its tensile strength can reach more than 1930 MPa and its elongation can reach more than 14%. In addition to its ultra-high strength characteristics, AerMet100 material also has high elastic modulus, high rigidity modulus and high toughness. It is usually used as a preparation material for key load-bearing structural parts such as aircraft landing gear, brake hook anchor rods, and fasteners. With the development and application of AerMet100 material, it has gradually become the preferred material for key transmission components such as aircraft engine bearings and gears. However, as a transmission component or when serving in a high temperature environment, higher requirements are placed on its surface performance. Therefore, AerMet100 steel needs to be surface hardened to improve its fatigue resistance and surface wear resistance.
[0003] At present, a variety of surface strengthening processes have been applied to high Co-Ni alloy materials to improve their surface hardness and fatigue resistance, such as laser cladding, plasma rare earth nitrocarburizing, low temperature ion nitrocarburizing and low temperature ion nitriding. According to relevant research results, the above processes will harden the surface of AerMet100 material and significantly improve the wear resistance of the material, but the generation of fatigue resistance strongly depends on the formation of residual compressive stress in the surface and subsurface of the material, and in the surface strengthening process, nitriding, shot peening or ultrasonic processes are generally used to meet the above requirements.
[0004] However, AerMet100 material is very sensitive to thermal processing technology. Although the ion nitriding process is more suitable for surface strengthening treatment of high alloy steel, when the temperature of the ion nitriding process is too high or too low, and the treatment time is too long or too short, the matrix of the AerMet100 material will continue to precipitate and grow due to the dispersion strengthening phase. The overall performance of the material will decrease and it will not be able to achieve the performance before nitriding, especially the impact on hardness and wear resistance is more obvious.
[0005] Therefore, it is an urgent problem to be solved by those skilled in the art to provide a low-temperature ion nitriding method that can form a nitriding layer on the surface of AerMet100 steel and improve the wear resistance of the material without reducing its hardness. Summary of the invention
[0006] In view of this, the present invention provides a low-temperature ion nitriding method for AerMet100 steel, which can complete the ion nitriding treatment at a relatively low temperature, thereby avoiding deformation of the AerMet100 steel during the ion nitriding treatment, while ensuring that the matrix hardness of the AerMet100 steel is not reduced, and has better comprehensive performance.
[0007] The present invention provides a method for low temperature ion nitriding of AerMet100 steel, comprising:
[0008] a) preheating AerMet100 steel to obtain preheated AerMet100 steel;
[0009] b) heat treating the preheated AerMet100 steel to obtain an AerMet100 steel sample, wherein the heat treatment includes solution treatment, cryogenic treatment and tempering treatment;
[0010] c) The AerMet100 steel sample is subjected to low temperature ion nitriding treatment to obtain AerMet100 steel containing a nitrided layer.
[0011] In some specific implementations, in step a, the temperature of the preheating treatment is 650°C to 900°C, the holding time of the preheating treatment is 1h to 2.5h, and the heating rate of the preheating treatment is 1°C / min to 20°C / min.
[0012] In some specific implementations, the preheating treatment further includes a cooling treatment, the cooling rate of the cooling treatment is 5°C / min to 20°C / min, and the final temperature of the cooling treatment is 20°C to 25°C.
[0013] In some specific implementations, step a) specifically includes: heating the AerMet100 steel from room temperature to 800°C at a heating rate of 10°C / min to 20°C / min, keeping the temperature for 10 to 30 minutes, heating the AerMet100 steel from 800°C to 900°C at a heating rate of 5°C / min to 10°C / min, and keeping the temperature for 1 to 2 hours; cooling the AerMet100 steel from 900°C to 750°C at a cooling rate of 5°C / min to 10°C / min, and then cooling the AerMet100 steel from 750°C to room temperature at a cooling rate of 10°C / min to 20°C / min; heating the AerMet100 steel from room temperature to 650°C at a heating rate of 5°C / min to 15°C / min, keeping the temperature for 10 to 20 minutes, heating the AerMet100 steel from 650°C to 680°C at a heating rate of 1°C / min to 5°C / min, and keeping the temperature for 8-10 hours. After cooling, the AerMet100 steel after preheat treatment is obtained.
[0014] In some specific implementations, the temperature of the solution treatment is 877° C. to 893° C., the holding time of the solution treatment is 1 h to 3 h, and the heating rate of the solution treatment is 1° C. / min to 20° C. / min;
[0015] The temperature of the cryogenic treatment is -81°C to -65°C, the holding time of the cryogenic treatment is 1h to 3h, and the cooling rate of the cryogenic treatment is 1°C / min to 20°C / min;
[0016] The temperature of the tempering treatment is 479° C. to 485° C., the holding time of the tempering treatment is 5 h to 8 h, and the heating rate of the tempering treatment is 1° C. / min to 20° C. / min.
[0017] In some specific implementations, the cross-sectional hardness of the AerMet100 steel sample is 53.5HRC to 54.5HRC.
[0018] In some specific implementations, the low-temperature ion nitriding treatment also includes a sputtering treatment before the treatment. The sputtering treatment lasts for 30 minutes to 60 minutes, the voltage of the sputtering treatment is -350V to -300V, the sputtering treatment is carried out under the condition of introducing hydrogen and nitrogen, the gas pressure of the sputtering treatment is 50Pa to 100Pa, and the flow ratio of hydrogen to nitrogen is 5:1 to 10:1.
[0019] In some specific implementations, the gas pressure of the low-temperature ion nitriding is 250Pa to 600Pa, the time of the low-temperature ion nitriding is 5h to 20h, and the voltage of the low-temperature ion nitriding treatment is -550V to -500V.
[0020] In some specific implementations, in step c, the AerMet100 steel sample is heated to 410°C to 440°C, the pressure is reduced to -480V to -450V for the first time, the gas pressure is increased to 250Pa to 600Pa, the flow ratio of hydrogen to nitrogen is reduced to 0.3:1 to 3:1, and then the pressure is reduced to -550V to -500V for the second time;
[0021] In some specific implementations, the heating rate is 1°C / min to 5°C / min, the first pressure reduction rate is 5V / min to 10V / min, the gas pressure increase rate is 20Pa / min to 50Pa / min, and the second pressure reduction rate is 5V / min to 10V / min.
[0022] In some specific implementations, the step c also includes grinding the AerMet100 steel sample, and the roughness of the AerMet100 steel sample after the grinding is 0.01 μm to 0.8 μm.
[0023] The present application first preheats AerMet100 steel to obtain preheated AerMet100 steel; heat treats the preheated AerMet100 steel to obtain an AerMet100 steel sample, wherein the heat treatment includes solution treatment, cryogenic treatment and tempering treatment; and low-temperature ion nitriding treatment is performed on the AerMet100 steel sample to obtain an AerMet100 steel containing a nitriding layer. The method can complete the ion nitriding treatment at a relatively low temperature, avoid deformation of the AerMet100 steel during the ion nitriding treatment, ensure that the matrix hardness of the AerMet100 steel is not reduced while forming a nitriding layer on the surface, and improve the wear resistance and fatigue resistance of the AerMet100 steel. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A flow chart of the method for low temperature ion nitriding of AerMet100 steel provided in this application;
[0025] Figure 2 The metallographic image of the AerMet100 ultra-high strength steel containing a nitrided layer provided in Example 1 of the present application;
[0026] Figure 3 The metallographic image of the AerMet100 ultra-high strength steel containing a nitrided layer provided in Example 2 of the present application;
[0027] Figure 4 The metallographic image of the AerMet100 ultra-high strength steel containing a nitrided layer provided in Example 3 of the present application;
[0028] Figure 5 A schematic diagram showing the distribution of hardness test points of the nitrided layer of the longitudinal section of the AerMet100 ultra-high strength steel containing a nitrided layer provided in Examples 1 to 3 of the present application;
[0029] Figure 6 A hardness trend diagram of the nitrided layer of the longitudinal section of the AerMet100 ultra-high strength steel containing the nitrided layer provided in Examples 1 to 3 of the present application;
[0030] Figure 7 A schematic diagram showing the distribution of the hardness test points of the cross-section of the AerMet100 ultra-high strength steel matrix containing a nitrided layer provided in Examples 1 to 3 of the present application;
[0031] Figure 8This is a residual stress trend diagram of the AerMet100 ultra-high strength steel containing a nitrided layer provided in Examples 1 to 3 of the present application. DETAILED DESCRIPTION
[0032] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.
[0033] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.
[0034] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.
[0035] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.
[0036] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.
[0037] The present application provides a method for low temperature ion nitriding of AerMet100 steel, comprising:
[0038] a) preheating AerMet100 steel to obtain preheated AerMet100 steel;
[0039] b) heat treating the preheated AerMet100 steel to obtain an AerMet100 steel sample, wherein the heat treatment includes solution treatment, cryogenic treatment and tempering treatment;
[0040] c) The AerMet100 steel sample is subjected to low temperature ion nitriding treatment to obtain AerMet100 steel containing a nitrided layer.
[0041] The present application uses AerMet100 steel as raw material, performs preheating treatment, heat treatment and low temperature ion nitriding treatment on it to prepare AerMet100 steel containing a nitrided layer. The AerMet100 steel includes but is not limited to AerMet100 ultra-high strength steel bars, and the present application has no special restrictions on the selection of AerMet100 steel.
[0042] See also Figure 1 , Figure 1 A flow chart of the method for low-temperature ion nitriding of AerMet100 steel provided in the present application, firstly, the AerMet100 steel is preheated to obtain the preheated AerMet100 steel; the AerMet100 steel is heat treated to obtain an AerMet100 steel sample; the AerMet100 steel sample is subjected to low-temperature ion nitriding to obtain an AerMet100 steel containing a nitrided layer.
[0043] The present application first preheats AerMet100 steel to obtain preheated AerMet100 steel. In some specific implementations, the preheating temperature is 650°C to 900°C, preferably 700°C to 850°C, the holding time is 1h to 2.5h, preferably 1.5h to 2h, and the heating rate is 1°C / min to 20°C / min, preferably 5°C / min to 10°C / min. In some specific implementations, the AerMet100 steel is heated from room temperature to 800°C at a heating rate of 10°C / min to 20°C / min, and kept warm for 10 to 30 minutes; the temperature is increased from 800°C to 900°C at a heating rate of 5°C / min to 10°C / min, and kept warm for 1 to 2 hours; the temperature is decreased from 900°C to 750°C at a cooling rate of 5°C / min to 10°C / min, and then the temperature is decreased from 750°C to room temperature at a cooling rate of 10°C / min to 20°C / min; the temperature is then increased from room temperature to 650°C at a heating rate of 5°C / min to 15°C / min, and kept warm for 10 to 20 minutes; the temperature is increased from 650°C to 680°C at a heating rate of 1°C / min to 5°C / min, and kept warm for 8-10 hours. After cooling, the preheat-treated AerMet100 steel is obtained.
[0044] The present application performs a cooling treatment on the AerMet100 steel after the preheating treatment to obtain the AerMet100 steel after the cooling treatment. In some specific implementations, the cooling rate of the cooling treatment is 5°C / min to 20°C / min, preferably 10°C / min to 15°C / min, and the final temperature of the cooling treatment is 20°C to 25°C, preferably 22°C to 24°C.
[0045] The present application then performs solution treatment, cryogenic treatment and tempering treatment on the AerMet100 steel after the cooling treatment to obtain an AerMet100 steel sample. In some specific implementations, the temperature of the solution treatment is 877°C to 893°C, preferably 880°C to 890°C, the holding time of the solution treatment is 1h to 3h, preferably 1.5h to 2.5h, the heating rate of the solution treatment is 1°C / min to 20°C / min, preferably 5°C / min to 10°C / min; the temperature of the cryogenic treatment is -81°C to -65°C, preferably -80°C to -70°C, the holding time of the cryogenic treatment is 1h to 3h, preferably -80℃ to -70℃, the cooling rate of the deep cryogenic treatment is 1℃ / min to 20℃ / min, preferably 5℃ / min to 10℃ / min; the temperature of the tempering treatment is 479℃ to 485℃, preferably 480℃ to 483℃, the holding time of the tempering treatment is 5h to 8h, preferably 5.5h to 7.5h, and the heating rate of the tempering treatment is 1℃ / min to 20℃ / min, preferably 5℃ / min to 10℃ / min. In some specific implementations, the cross-sectional hardness of the AerMet100 steel sample is 53.5HRC to 54.5HRC, which can be 53.5HRC, 53.6HRC, 53.7HRC, 53.8HRC, 53.9HRC, 54HRC, 54.1HRC, 54.2HRC, 54.3HRC, 54.4HRC, 54.5HRC.
[0046] The present application then grinds the heat-treated AerMet100 steel to obtain a grinded AerMet100 steel sample. In some specific implementations, the roughness of the AerMet100 steel sample after grinding is 0.01 μm to 0.8 μm, preferably 0.01 μm to 0.4 μm. In some specific implementations, the grinding process includes: grinding the outer surface and the upper and lower planes of the AerMet100 steel sample as a whole, and wiping it clean with acetone, and the roughness of the AerMet100 steel sample after grinding is 0.01 μm to 0.8 μm.
[0047] The present application performs sputtering treatment on the polished AerMet100 steel to obtain the sputtered AerMet100 steel. In some specific implementations, the sputtering treatment time is 30 min to 60 min, preferably 35 min to 55 min, and the sputtering treatment voltage is -350 V to -300 V, preferably -340 V to -310 V. In some specific implementations, the sputtering treatment is carried out under the condition of introducing hydrogen and nitrogen, the gas pressure of the sputtering treatment is 50 Pa to 100 Pa, preferably 60 Pa to 90 Pa, and the flow ratio of hydrogen to nitrogen is 5:1 to 10:1, preferably 6:1 to 8:1.
[0048] The specific operation of the sputtering treatment is as follows: placing the heat-treated AerMet100 steel sample on the cathode disk in the ion nitriding furnace, closing the furnace cover and ensuring good sealing; evacuating the furnace chamber of the ion nitriding furnace to a vacuum of no more than 10Pa, then introducing nitrogen into the furnace chamber until the air pressure in the furnace chamber rises to 0.6-0.9bar, and then turning on the heating power supply to heat the ion nitriding furnace; when the temperature in the ion nitriding furnace rises to 300°C to 350°C, evacuating the furnace chamber again to a vacuum of no more than 10Pa, then introducing hydrogen and nitrogen into the furnace chamber at the same time until the air pressure in the furnace chamber rises to 50-100Pa, and then turning on the ion power supply; while keeping the hydrogen and nitrogen introduced, sputtering the surface of the AerMet100 steel sample until the passivation film on the surface of the AerMet100 steel sample is removed.
[0049] The present application then performs low-temperature ion nitriding treatment on the AerMet100 steel sample after the sputtering treatment to obtain AerMet100 steel containing a nitrided layer. In some specific implementations, the gas pressure of the low-temperature ion nitriding is 250Pa to 600Pa, preferably 300Pa to 500Pa; the time of the low-temperature ion nitriding is 5h to 20h, preferably 10h to 18h, and the voltage of the low-temperature ion nitriding treatment is -550V to -500V, preferably -540V to -520V.
[0050] In some specific implementations, the AerMet100 steel sample is heated to 410°C to 440°C, the pressure is reduced to -480V to -450V for the first time, the pressure is increased to 250Pa to 600Pa, the flow ratio of hydrogen to nitrogen is reduced to 0.3:1 to 3:1, and then the pressure is reduced to -550V to -500V for the second time; the heating rate is 1°C / min to 5°C / min, the first pressure reduction rate is 5V / min to 10V / min, the pressure increase rate is 20Pa / min to 50Pa / min, and the second pressure reduction rate is 5V / min to 10V / min. In some specific implementations, the flow ratio of hydrogen to nitrogen is reduced to 1:1 to 2:1.
[0051] In some specific implementations, the AerMet100 steel sample is heated to 410°C~440°C, and the voltage is reduced to -480V~-450V for the first time. After the temperature rise and the voltage drop in the ion nitriding furnace are completed, the flow ratio of hydrogen and nitrogen is reduced to 0.3:1~3:1, and the gas pressure is increased to 250Pa~600Pa; after the gas pressure rise and the flow ratio of hydrogen and nitrogen in the ion nitriding furnace are completed, the voltage is reduced to -550V~-500V for the second time; after the temperature, voltage, gas pressure, and flow ratio of hydrogen and nitrogen in the ion nitriding furnace reach the designed conditions, low-temperature ion nitriding is carried out. After the low-temperature ion nitriding treatment is completed, the heating power supply and ion power supply of the ion nitriding furnace are turned off, and the introduction of hydrogen is stopped at the same time, and the introduction of nitrogen is maintained. Then, the fan is turned on to reduce the temperature in the furnace chamber to below 150°C to obtain AerMet100 steel containing a nitrided layer.
[0052] The present invention is further described below in conjunction with the following examples. The protection scope of the present invention is not limited by the following examples.
[0053] Example 1
[0054] A cylindrical AerMet100 ultra-high strength steel bar with a diameter of 30 mm was placed in a heat treatment furnace, and the temperature was increased from room temperature to 800°C at a heating rate of 15°C / min, and kept warm for 20 minutes. Then, the temperature was increased from 800°C to 900°C at a heating rate of 8°C / min, and kept warm for 1.5 hours. Then, the temperature was reduced from 900°C to 750°C at a cooling rate of 8°C / min, and then the temperature was reduced from 750°C to room temperature at a cooling rate of 15°C / min. Argon was introduced during the heating and cooling process, and the flow rate of argon was 80L / min.
[0055] The AerMet100 ultra-high strength steel bar is put into the heat treatment furnace again, and the temperature is increased from room temperature to 650°C at a heating rate of 10°C / min, and kept warm for 15 minutes. Then, the temperature is increased from 650°C to 680°C at a heating rate of 3°C / min, and kept warm for 9 hours. Then, the steel bar is cooled with the furnace to obtain the AerMet100 ultra-high strength steel bar after preheat treatment. Argon gas is introduced during the heating and cooling processes, and the flow rate of argon gas is 80L / min.
[0056] The AerMet100 ultra-high strength steel bar after preheat treatment is placed in a vacuum furnace at 885°C for solution treatment for 1 hour, and then taken out for oil quenching cooling; then the AerMet100 ultra-high strength steel bar is placed in a cold treatment furnace at -73°C for deep cold treatment for 1 hour, and then taken out and naturally warmed to room temperature; then the AerMet100 ultra-high strength steel bar is placed in an air furnace at 482°C for tempering treatment for 5 hours, and then taken out and air-cooled to obtain the heat-treated AerMet100 ultra-high strength steel with a hardness of 54HRC, i.e. 578HV.
[0057] AerMet100 ultra-high strength steel specimens with a diameter of 30 mm and a height of 20 mm were cut from the heat-treated AerMet100 ultra-high strength steel by wire cutting; the surface of the AerMet100 ultra-high strength steel specimen was overall polished and wiped clean with an organic solvent. After overall polishing, the roughness of the AerMet100 ultra-high strength steel specimen was 0.45 μm.
[0058] The AerMet100 ultra-high strength steel sample was placed on the cathode disk in the ion nitriding furnace, and the furnace cover was closed to ensure good sealing; the furnace chamber of the ion nitriding furnace was evacuated to 10Pa, and then nitrogen was introduced into the furnace chamber until the gas pressure in the furnace chamber increased to 0.8bar, and then the heating power was turned on to heat the ion nitriding furnace; after the temperature in the ion nitriding furnace increased to 320°C, it was evacuated to 10Pa again, and then hydrogen and nitrogen were simultaneously introduced into the furnace chamber (the flow ratio of hydrogen to nitrogen was 8:1) until the gas pressure in the furnace chamber increased to 80Pa, and then the ion power was turned on; while keeping the hydrogen and nitrogen introduced, the surface of the AerMet100 ultra-high strength steel sample was sputtered for 45 minutes at a sputtering voltage of -320V to obtain the AerMet100 ultra-high strength steel sample with the passivation film removed.
[0059] The temperature in the ion nitriding furnace was increased from 320°C to 425°C at a heating rate of 3°C / min, and then the voltage in the ion nitriding furnace was reduced from -320V to -465V at a pressure reduction rate of 8V / min, and the gas pressure in the ion nitriding furnace was increased from 80Pa to 425Pa at a pressure increase rate of 35Pa / min, and the flow ratio of hydrogen to nitrogen was reduced from 8:1 to 1.5:1, and the voltage in the ion nitriding furnace was reduced from -465V to -525V at a pressure reduction rate of 8V / min. Then, the AerMet100 ultra-high strength steel sample was subjected to low-temperature ion nitriding treatment for 12 hours, and the heating power supply and ion power supply of the ion nitriding furnace were turned off, and the introduction of hydrogen was stopped at the same time, and the introduction of nitrogen was maintained until the gas pressure in the ion nitriding furnace was reduced to 0.8bar, and then the fan was turned on to reduce the temperature in the furnace chamber to 150°C to obtain AerMet100 ultra-high strength steel containing a nitrided layer.
[0060] Example 2
[0061] A cylindrical AerMet100 ultra-high strength steel bar with a diameter of 30 mm was placed in a heat treatment furnace, and the temperature was increased from room temperature to 800°C at a heating rate of 10°C / min, and kept warm for 30 minutes; the temperature was increased from 800°C to 900°C at a heating rate of 5°C / min, and kept warm for 2 hours; the temperature was reduced from 900°C to 750°C at a cooling rate of 5°C / min, and then reduced from 750°C to room temperature at a cooling rate of 10°C / min, and then the AerMet100 ultra-high strength steel bar was taken out; argon gas was introduced during the heating and cooling process, and the argon gas flow rate was 50L / min.
[0062] The AerMet100 ultra-high strength steel bar was put into the heat treatment furnace again, and the temperature was increased from room temperature to 650°C at a heating rate of 5°C / min, and kept warm for 20 minutes; the temperature was increased from 650°C to 680°C at a heating rate of 1°C / min, and kept warm for 10 hours, and then cooled with the furnace to obtain the treated AerMet100 ultra-high strength steel bar; argon gas was introduced during the heating and cooling processes, and the argon gas flow rate was 50L / min.
[0063] The AerMet100 ultra-high strength steel bar after preheat treatment is placed in a vacuum furnace at 885°C for solution treatment for 1 hour, and then taken out for oil quenching cooling; then the AerMet100 ultra-high strength steel bar is placed in a cold treatment furnace at -73°C for deep cold treatment for 1 hour, and then taken out and naturally warmed to room temperature; finally, the AerMet100 ultra-high strength steel bar is placed in an air furnace at 482°C for tempering treatment for 5 hours, and then taken out and air-cooled to obtain the heat-treated AerMet100 ultra-high strength steel with a hardness of 54HRC, i.e. 578HV.
[0064] AerMet100 ultra-high strength steel specimens with a diameter of 30 mm and a height of 20 mm were cut from the heat-treated AerMet100 ultra-high strength steel by wire cutting; the surface of the AerMet100 ultra-high strength steel specimen was overall polished and wiped clean with an organic solvent. After overall polishing, the roughness of the AerMet100 ultra-high strength steel specimen was 0.45 μm.
[0065] The AerMet100 ultra-high strength steel sample was placed on the cathode disk in the ion nitriding furnace, and the furnace cover was closed and ensured to be well sealed; the furnace chamber of the ion nitriding furnace was evacuated to 10Pa, and then nitrogen was introduced into the furnace chamber until the gas pressure in the furnace chamber increased to 0.6bar, and then the heating power was turned on to heat the ion nitriding furnace; after the temperature in the ion nitriding furnace increased to 300°C, it was evacuated to 10Pa again, and then hydrogen and nitrogen were simultaneously introduced into the furnace chamber (the flow ratio of hydrogen to nitrogen was 5:1) until the gas pressure in the furnace chamber increased to 50Pa, and then the ion power was turned on; while keeping the hydrogen and nitrogen introduced, the surface of the AerMet100 ultra-high strength steel sample was sputtered for 60 minutes at a sputtering voltage of -350V to obtain the AerMet100 ultra-high strength steel sample with the passivation film removed.
[0066] The temperature in the ion nitriding furnace was increased from 300°C to 410°C at a heating rate of 1°C / min; the voltage in the ion nitriding furnace was reduced from -350V to -480V at a pressure reduction rate of 5V / min; then the gas pressure in the ion nitriding furnace was increased from 50Pa to 250Pa at a pressure increase rate of 20Pa / min, and the flow ratio of hydrogen to nitrogen was reduced from 5:1 to 0.3:1; then the voltage in the ion nitriding furnace was reduced from -480V to -550V at a pressure reduction rate of 5V / min; the AerMet100 ultra-high strength steel sample was started to be subjected to low-temperature ion nitriding treatment for 5h; the heating power supply and ion power supply of the ion nitriding furnace were turned off, and the hydrogen supply was stopped at the same time, and the nitrogen supply was kept until the gas pressure in the ion nitriding furnace was reduced to 0.6bar, and then the fan was turned on to reduce the temperature in the furnace chamber to 150°C to obtain the AerMet100 ultra-high strength steel containing a nitrided layer.
[0067] Example 3
[0068] A cylindrical AerMet100 ultra-high strength steel bar with a diameter of 30 mm was placed in a heat treatment furnace, and the temperature was increased from room temperature to 800°C at a heating rate of 20°C / min, and kept warm for 10 minutes; the temperature was increased from 800°C to 900°C at a heating rate of 10°C / min, and kept warm for 1 hour; the temperature was reduced from 900°C to 750°C at a cooling rate of 10°C / min, and then reduced from 750°C to room temperature at a cooling rate of 20°C / min, and then the AerMet100 ultra-high strength steel bar was taken out; argon gas was introduced during the heating and cooling process, and the argon gas flow rate was 100L / min.
[0069] The AerMet100 ultra-high strength steel bar was put into the heat treatment furnace again, and the temperature was increased from room temperature to 650°C at a heating rate of 15°C / min, and kept warm for 10 minutes; the temperature was increased from 650°C to 680°C at a heating rate of 5°C / min, and kept warm for 8 hours, and then cooled with the furnace to obtain the AerMet100 ultra-high strength steel bar after preheat treatment; argon gas was introduced during the heating and cooling processes, and the argon gas flow rate was 100L / min.
[0070] The AerMet100 ultra-high strength steel bar after preheat treatment is placed in a vacuum furnace at 885°C for solution treatment for 1 hour, and then taken out for oil quenching cooling; then the AerMet100 ultra-high strength steel bar is placed in a cold treatment furnace at -73°C for deep cold treatment for 1 hour, and then taken out and naturally warmed to room temperature; finally, the AerMet100 ultra-high strength steel bar is placed in an air furnace at 482°C for tempering treatment for 5 hours, and then taken out and air-cooled to obtain the heat-treated AerMet100 ultra-high strength steel with a hardness of 54HRC, i.e. 578HV.
[0071] AerMet100 ultra-high strength steel specimens with a diameter of 30 mm and a height of 20 mm were cut from the heat-treated AerMet100 ultra-high strength steel by wire cutting; the surface of the AerMet100 ultra-high strength steel specimen was overall polished and wiped clean with an organic solvent. After overall polishing, the roughness of the AerMet100 ultra-high strength steel specimen was 0.45 μm.
[0072] The AerMet100 ultra-high strength steel sample was placed on the cathode disk in the ion nitriding furnace, and the furnace cover was closed to ensure good sealing; the furnace chamber of the ion nitriding furnace was evacuated to 10Pa, and then nitrogen was introduced into the furnace chamber until the gas pressure in the furnace chamber increased to 0.9bar, and then the heating power was turned on to heat the ion nitriding furnace; when the temperature in the ion nitriding furnace increased to 350°C, it was evacuated to 10Pa again, and then hydrogen and nitrogen were simultaneously introduced into the furnace chamber (the flow ratio of hydrogen to nitrogen was 10:1) until the gas pressure in the furnace chamber increased to 100Pa, and then the ion power was turned on; while keeping the hydrogen and nitrogen introduced, the surface of the AerMet100 ultra-high strength steel sample was sputtered for 30 minutes at a sputtering voltage of -300V to obtain the AerMet100 ultra-high strength steel sample with the passivation film removed.
[0073] The temperature in the ion nitriding furnace was increased from 350°C to 440°C at a heating rate of 5°C / min, and the voltage in the ion nitriding furnace was reduced from -300V to -450V at a pressure reduction rate of 10V / min; the gas pressure in the ion nitriding furnace was increased from 100Pa to 600Pa at a pressure increase rate of 50Pa / min, and the flow ratio of hydrogen to nitrogen was reduced from 10:1 to 3:1; the voltage in the ion nitriding furnace was reduced from -450V to -500V at a pressure reduction rate of 10V / min; the AerMet100 ultra-high strength steel sample was started to be subjected to low-temperature ion nitriding treatment for 20h; the heating power supply and ion power supply of the ion nitriding furnace were turned off, and the hydrogen supply was stopped at the same time, and the nitrogen supply was kept until the gas pressure in the ion nitriding furnace was reduced to 0.9bar, and then the fan was turned on to reduce the temperature in the furnace chamber to 150°C to obtain the AerMet100 ultra-high strength steel containing a nitrided layer.
[0074] The morphology of the nitrided layer and the matrix of the AerMet100 steel containing the nitrided layer provided in Examples 1 to 3 was observed by an optical metallographic microscope. The metallographic image of the longitudinal section of the AerMet100 steel containing the nitrided layer is as follows: Figures 2 to 4 As shown in the figure, it can be seen that the nitrided structure of the AerMet100 ultra-high strength steel samples in the three embodiments only has typical supersaturated martensite, and no white bright layer or vein structure is seen.
[0075] For the AerMet100 steel with nitriding layer provided in Examples 1 to 3, the hardness gradient of the nitriding layer was measured using a Vickers hardness tester with a load of 200 g and a loading time of 30 seconds. Nitrogen atoms gradually penetrate from the surface of the AerMet100 ultra-high strength steel sample to the inside to form a nitriding layer. The distribution of the hardness test points of the nitriding layer on the longitudinal section of the AerMet100 steel with nitriding layer is shown in FIG. Figure 5As shown in the figure, the longitudinal section of the sample is a rectangle with a long side of 30 mm and a short side of 20 mm. The center line of the long side is used as the reference, and broken lines are drawn on both sides of the center line. Finally, the hardness is measured on the center line of the long side and the end points of the broken lines. A total of ten points are measured, and the vertical distances between each point and the long side of the sample (i.e., the sample surface) are 0μm, 30μm, 45μm, 60μm, 75μm, 90μm, 110μm, 130μm, 150μm, and 170μm, respectively. The hardness trend of the nitrided layer on the longitudinal section of AerMet100 steel containing a nitrided layer is shown in the figure. Figure 6 As shown in the figure, it can be seen that the nitrided layers of the AerMet100 steel containing nitrided layers in the three embodiments all form a typical nitrided hardness gradient distribution, and the hardness of the sample surface reaches between 1100-1200 HV.
[0076] For the AerMet100 steel with nitriding layer provided in Examples 1 to 3, the hardness gradient of the substrate was measured using a Rockwell hardness tester with a load of 120 kg and a loading time of 10 s. The distribution of the substrate hardness test points on the cross section of the AerMet100 steel with nitriding layer is shown in FIG. Figure 7 As shown, the cross section of the sample is circular with a diameter of 30 mm. Taking the center of the circle as the reference, two circles are drawn outward with radii of 7.5 mm and 10 mm respectively. Finally, a hardness value is measured at the center of the circle, four hardness values are evenly measured on the circumference of a circle with a radius of 7.5 mm, and four hardness values are evenly measured on the circumference of a circle with a radius of 10 mm. The hardness measurement points on the two circumferences are staggered, and the hardness values of each measurement point are shown in Table 1.
[0077] Table 1
[0078]
[0079] From the data shown in Table 1, the matrix hardness of AerMet100 steel containing a nitriding layer is maintained within the range of 54±0.5HRC, which means that while a nitriding layer is formed on the surface of AerMet100 ultra-high strength steel, the matrix hardness of AerMet100 ultra-high strength steel can be ensured not to decrease.
[0080] For the AerMet100 steel containing a nitriding layer provided in Examples 1 to 3, the surface roughness of the AerMet100 steel containing a nitriding layer before and after nitriding was measured using a roughness measuring instrument, and each sample was measured three times, and the average value was finally taken. The measurement results are shown in Table 2. From the data shown in Table 2, it can be seen that the surface roughness of the AerMet100 ultra-high strength steel before and after nitriding remains basically unchanged, and the average roughness is controlled at about 0.45 μm.
[0081] Table 2
[0082]
[0083] For the above three embodiments, the residual stress of the nitrided layer was tested by XRD residual stress analyzer. The residual stress trend of AerMet100 steel containing nitrided layer is as follows: Figure 8 As shown. It can be seen from the figure that the residual compressive stress of AerMet100 steel containing a nitriding layer decreases with the increase of the nitriding depth, forming a gradient structure similar to the hardness curve. Among them, the residual stress of the nitriding layer of the three embodiments all reaches about -1000 MPa, and this high pressure stress state can be maintained for a distance near the surface of the sample. In addition, the nitriding layers of the three embodiments have positive stress at depths of 75μm, 89μm and 112μm, respectively. According to the residual stress test results, as the nitriding time increases, the residual compressive stress will appear deeper in the sample, which corresponds to the relationship between the nitriding time and the hardness distribution of the nitriding layer, that is, the deeper the nitriding layer, the greater the residual compressive stress and the better the fatigue resistance.
[0084] The AerMet100 steel containing a nitrided layer provided in Examples 1 to 3 was subjected to a rotary bending fatigue test using a rotary bending fatigue testing machine. The test temperature was room temperature, Kt=1, the rotation speed was 3000 rpm, and each sample was tested three times. The test results are shown in Table 3.
[0085] Table 3
[0086]
[0087] From the data in Table 3, when the maximum stress is 980 MPa, the number of cycles of the AerMet100 ultra-high strength steel sample before nitriding is 1.1×10 6 The number of cycles of the AerMet100 ultra-high strength steel sample after nitriding is 8.1-9.3×10 6 It can be seen that the fatigue resistance of AerMet100 steel containing nitriding layer has been greatly improved.
[0088] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for low temperature ion nitriding of AerMet100 steel, characterized in that: include: a) preheating AerMet100 steel to obtain preheated AerMet100 steel; b) heat treating the preheated AerMet100 steel to obtain an AerMet100 steel sample, wherein the heat treatment includes solution treatment, cryogenic treatment and tempering treatment; c) The AerMet100 steel sample is subjected to low temperature ion nitriding treatment to obtain AerMet100 steel containing a nitrided layer.
2. The method according to claim 1, characterized in that In the step a, the temperature of the preheating treatment is 650° C. to 900° C., the holding time of the preheating treatment is 1 h to 2.5 h, and the heating rate of the preheating treatment is 1° C. / min to 20° C. / min.
3. The method according to claim 1, characterized in that The preheating treatment also includes a cooling treatment, the cooling rate of the cooling treatment is 5°C / min to 20°C / min, and the final temperature of the cooling treatment is 20°C to 25°C.
4. The method according to claim 1, characterized in that: Step a) specifically comprises: heating the AerMet100 steel from room temperature to 800°C at a heating rate of 10°C / min to 20°C / min, keeping the temperature for 10min to 30min, heating the AerMet100 steel from 800°C to 900°C at a heating rate of 5°C / min to 10°C / min, and keeping the temperature for 1h to 2h; cooling the AerMet100 steel from 900°C to 750°C at a cooling rate of 5°C / min to 10°C / min, and then cooling the AerMet100 steel from 750°C to room temperature at a cooling rate of 10°C / min to 20°C / min; heating the AerMet100 steel from room temperature to 650°C at a heating rate of 5°C / min to 15°C / min, keeping the temperature for 10min to 20min, heating the AerMet100 steel from 650°C to 680°C at a heating rate of 1°C / min to 5°C / min, and keeping the temperature for 8-10h. After cooling, the AerMet100 steel after preheat treatment is obtained.
5. The method according to claim 1, characterized in that The temperature of the solution treatment is 877°C to 893°C, the holding time of the solution treatment is 1h to 3h, and the heating rate of the solution treatment is 1°C / min to 20°C / min; The temperature of the cryogenic treatment is -81°C to -65°C, the holding time of the cryogenic treatment is 1h to 3h, and the cooling rate of the cryogenic treatment is 1°C / min to 20°C / min; The temperature of the tempering treatment is 479° C. to 485° C., the holding time of the tempering treatment is 5 h to 8 h, and the heating rate of the tempering treatment is 1° C. / min to 20° C. / min.
6. The method according to claim 1, characterized in that The cross-sectional hardness of the AerMet100 steel specimen is 53.5 HRC to 54.5 HRC.
7. The method according to claim 1, characterized in that The low-temperature ion nitriding treatment also includes sputtering treatment before the treatment. The sputtering treatment time is 30 minutes to 60 minutes, the voltage of the sputtering treatment is -350V to -300V, the sputtering treatment is carried out under the condition of hydrogen and nitrogen, the gas pressure of the sputtering treatment is 50Pa to 100Pa, and the flow ratio of hydrogen to nitrogen is 5:1 to 10:
1.
8. The method according to claim 1, characterized in that The gas pressure of the low-temperature ion nitriding is 250Pa to 600Pa, the time of the low-temperature ion nitriding is 5h to 20h, and the voltage of the low-temperature ion nitriding treatment is -550V to -500V.
9. The method according to claim 8, characterized in that In the step c, the AerMet100 steel sample is heated to 410°C to 440°C, the pressure is reduced to -480V to -450V for the first time, the pressure is increased to 250Pa to 600Pa, the flow ratio of hydrogen to nitrogen is reduced to 0.3:1 to 3:1, and then the pressure is reduced to -550V to -500V for the second time; The heating rate is 1°C / min to 5°C / min, the first pressure reduction rate is 5V / min to 10V / min, the gas pressure increasing rate is 20Pa / min to 50Pa / min, and the second pressure reduction rate is 5V / min to 10V / min.
10. The method according to claim 1, characterized in that Before step c, the method further includes grinding the AerMet100 steel sample, wherein the roughness of the AerMet100 steel sample after the grinding process is 0.01 μm to 0.8 μm.
Citation Information
Patent Citations
Boron-containing surface modification layer steel and preparation method thereof
CN117107143A
Nitriding crack control method for martensite thermal strength stainless steel material part
CN117488237A
Cast iron low-temperature tufftriding system and process
CN118531337A
Hardened Martensitic Steel Having a Low Cobalt Content, Process for Manufacturing a Part from Steel, and Part thus Obtained
US20110226386A1